CORRELATION OF THE PHISICAL PROPERTIES AND MORPHOLOGICAL SIGNS OF THE HUMAN HEART VALVES IN NORM IN THE CONTEXT OF THE LASER POLARIMETRY - Semeniuk, T. (World of Medicine and Biology, 2014)
Background. The increasing of the cardio-vascular diseases [3] to increase the necessity of the modern medicine for the detail understanding of the structural and functional tissue and cellular changes that are happened with age in the human heart and its valves [1, 4]. These changes can case the acquired heart diseases [7, 8]. Heart valves are described in a lot of scientific works [2, 5, 10, 12, 13, 14], but there is the discussion about the presence of the blood vessels within the heart valves, their origin and morphological features. This theme is an actual for today due to the necessity of the modern medicine. Aim. The article is devoted to the investigation of the leaflets of the human heart valves. The aim of the investigation is to study the structure, particularities of the blood supply and to receive the optic characteristics, which possible be received using the method of the laser polarimetry. Objects and methods. The infants’ heart valves and heart valves of the people of mature age were used for the investigation. The light microscopy, histochemical, immunohistochemical methods and methods of the laser polarimetry and 3D reconstruction were used. Results. The leaflets of human heart valves during the postnatal ontogenesis obtain the distinct three-layered structure that was detected in results. Three layers: spongy, fibrous and ventricular were identified within them. The layers are made of fibrous connective tissues. The blood vessels: muscular arteries, arterioles, capillaries, venules and muscular veins were seen within the heart valves. The blood vessels are present in the base of leaflets of the atria-ventricular valves in people of mature age. The positive reactions were received on the СD 34 and α-sma, which confirm the presence of the blood vessels within the leaflets of the human heart valves. The results which were taken on laser polarimetry investigation confirm the three-layered structure of the heart valves. The collagen and elastic fibers were detected within the more dense layers of leaflets with the predomination one another correspond to the layer. The method of 3D reconstruction confirms: the area of the magistral blood vessels within the chordae tendinea of the atria-ventricular valves toward the leaflet is from 5,3 % to 5,9 % in the mitral and from 2,8 % to 3,3 % in the tricuspid valves. The magistral blood vessels give branches for the vessels of the microcirculatory bed in the area of the attachment of chordae tendinea to the leaflets. The area of the blood vessels of microcirculation is increased into 2 times within the leaflet of the mitral and into 4 times within the leaflet of the tricuspid valves. Conclusions. The using the histological methods and method of laser polarimetry detect that during the postnatal period of human ontogenesis in the human heart valves are happen changes due to which within the leaflets of the heart valves appear three layers. Human heart valves contain the blood vessels: the blood inflow is due to the muscular arteries and arterioles; the blood circulation due to the somatic capillaries; the blood outflow is due to the venules and unmuscular veins. The blood vessels are placed in the basal region of the leaflet. The area of the magistral blood vessels within the chordae tendinea of the atrioventricular valves is 5,3 % till 5,9 % in the mitral valve and 2,8 % till 3,3 % in the tricuspid valve. Within the leaflet of the heart valve the magistral blood vessels have branches and their area within the leaflets increases: in the mitral valve into 2 times, in the tricuspid valve into 4 times.